جودة الرعاية الصحية بالمستشفيات الحكومية من وجهة نظر الطاقم الطبي وعلاقتها بالأداء الإجتماعي - بوعبدالله, مصطفى (جامعة الوادي University of Eloued, 2025)
This study aims to assess the quality of healthcare services using the Servqual model and examine its relationship with the achievement of social performance at the level of Beni Saf Public Hospital. To accomplish this, a sample of 53 medical staff members was selected. A questionnaire was distributed and analyzed using SPSS V25. The study's results indicated that there is no statistically significant relationship between healthcare quality and social performance at the 0.05 significance level at Beni Saf Public Hospital. Furthermore, no significant impact of healthcare quality on social performance was observed at the same significance level. However, the quality of healthcare was found to have a statistically significant effect on the human dimension of social performance, while it showed no significant effect on the environmental or societal dimensions. Finally, the study concluded with several necessary recommendations that could be adopted in healthcare institutions.
The Quality of Healthcare in Public Hospitals from the Perspective of Medical Staff and Its Relationship with Social Performance: A Case Study of Beni Saf Public Hospital.
مقال
Keywords: رعاية الصحية; جودة الخدمة; أداء إجتماعي; طاقم طبي